2010
DOI: 10.1088/0952-4746/30/2/s01
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the environment from ionising radiation in a regulatory context—an overview of the PROTECT coordinated action project

Abstract: The outcome of the PROTECT project (Protection of the Environment from Ionising Radiation in a Regulatory Context) is summarised, focusing on the protection goal and derivation of dose rates which may detrimentally affect wildlife populations. To carry out an impact assessment for radioactive substances, the estimated dose rates produced by assessment tools need to be compared with some form of criteria to judge the level of risk. To do this, appropriate protection goals need to be defined and associated prede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…To assess the risk for each contaminated wetland is beyond the scope of this study but for the purpose of comparison to a screening value of 10 mGy h À1 , below which ecosystems are to be protected (Howard et al, 2010), all but one predicted dose in Steel Creek Swamp exceeded 10 mGy h À1 . For Utnora Swamp three predicted doses were above 10 mGy h À1 , while measurements showed that actual levels were up to two orders of magnitude lower.…”
Section: General Aspectsmentioning
confidence: 99%
“…To assess the risk for each contaminated wetland is beyond the scope of this study but for the purpose of comparison to a screening value of 10 mGy h À1 , below which ecosystems are to be protected (Howard et al, 2010), all but one predicted dose in Steel Creek Swamp exceeded 10 mGy h À1 . For Utnora Swamp three predicted doses were above 10 mGy h À1 , while measurements showed that actual levels were up to two orders of magnitude lower.…”
Section: General Aspectsmentioning
confidence: 99%
“…High priority CRwo-soil values have been defined as those where: (i) the contribution of internal dose to the total weighted absorbed dose rate was above 70%, and (ii) the internal weighted absorbed dose rate was above 1E-3 μGy h −1 , assuming 1 Bq kg −1 dw soil. The choice of criteria values was partially based on a comparison with the 10 μGy h −1 default screening value in the ERICA Tool (Larsson, 2008;Howard et al, 2010;GarnierLaPlace et al 2008;Andersson et al, 2009). For example, assuming 1 Bq kg −1 dw in soil, an estimated internal dose rate of 1E-3 μGy h −1 means that 10,000 Bq kg −1 dw would be required in soil to result in a dose rate of 10 μGy h −1 .…”
Section: 2mentioning
confidence: 99%
“…Assessing the biological impact of ionising radiation on nonhuman biota has been identified as a necessary approach towards protecting and mitigating the impacts of future radioactive releases on the environment by a number of international directives (e.g. ERICA and PROTECT [Howard et al, 2010;Larsson, 2008]). …”
Section: Introductionmentioning
confidence: 99%